The propylitic alteration in the Ponce Enriquez Gold Mining district, Azuay province, Ecuador: genetic constraints from a mineral chemistry and fluid inclusions study - Fulignati, Paolo; Mulas, Maurizio; Villalta Echeverria, Michelle Del Pilar; Fornasaro, Silvia; Larreta, Erwin; Mendoza Arteaga, Pierina Lisbeth; Menoscal Menoscal, Melanie Annabela; Romero-Crespo, Paola; Gioncada, Anna (Frontiers in Earth Science, 2023)
Wide areas of the Southern sector of Ecuador are characterized by Cretaceous mafic volcanic rocks, pervasively altered by a propylitic mineralogical assemblage with epidote, chlorite, and quartz with minor titanite, illite and prehnite. These propylitically altered rocks host significant gold mineralization in veins, deeply exploited in the last decades, and associated to porphyry Au-Cu deposits. This work focuses on the study of this propylitic alteration to assess the genetic conditions and the relation with the distance from the porphyry system, through the chemical composition of the secondary minerals (particularly trace elements in epidote and chlorite) and fluid inclusion data. The aim is to improve knowledge of the trace element geochemistry of secondary minerals in propylitic alteration and their relationship to the causative porphyry systems. The results of this work indicate that alteration affecting the rocks of the Pallatanga Fm. can be related to the propylitic hydrothermal alteration halo of porphyry copper deposits. Fluid inclusion investigation in quartz veins associated with epidote and chlorite evidenced at least two pulses of hydrothermal fluids characterized by temperature around 345 °C for the first one and around 305 °C for the second one. The salinity of the fluids is always low (around 1.5 wt.% NaClequiv.) suggesting a dominantly meteoric component. Evidence of boiling processes have not been observed. We hypothesize that the hydrothermally altered "green rocks" of the Ponce Enriquez Mining District could be envisaged as the propylitic halo of the Miocene hornblende-bearing Au-Cu porphyry deposits of Gaby-Papa Grande, and discuss the epidote and chlorite trace element composition in this scenario. The results help improving the general knowledge of the propyliticallyThe PEMD (Azuay Province) is sited in southern Ecuador on the western flank of the Western Cordillera and is comprised between two hydrographic basins: the Río Siete basin to the south and the Río Guanache basin to the north (Figure 1). The Pallatanga Fm., the Yunguilla Fm., and the Saraguro Group (Las Trancas Fm.) outcrop in this area (Figure 1) (PRODEMINCA, 2000). The Pallatanga Fm.